2018
DOI: 10.1007/s10803-018-3857-6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adaptive Behavior and Parent Expectations in Predicting Post-School Outcomes for Young Adults with Intellectual Disability

Abstract: This study examined the role of parent expectations and adaptive behavior in predicting outcomes for youth with intellectual disability. The study addresses the following research aims: (1) Describe post-school outcomes and parent expectations for individuals with mild and moderate/severe intellectual disability, (2) Determine the relationship of adaptive functioning and parent expectations to post-school outcomes (i.e., postsecondary education, employment, and independent living) for individuals with intellec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 52 publications
0
19
0
1
Order By: Relevance
“…In young children, adaptive behavior measures consider a wide range of developmentally relevant constructs known to affect early childhood outcomes, such as executive functioning, behavioral inhibition, social-emotional skills, and pre-academic skills (Luckasson et al, 2002 ; Sparrow et al, 2005 ; Oakland and Harrison, 2008 ). Thus, adaptive behavior may serve as a proximal indication of how an individual functions within developmentally relevant contexts and provide additional information important for conceptualizing the profile of risk of an individual child and resilience in their specific environment (Test et al, 2009 ; Bal et al, 2015 ; Dell'Armo and Tassé, 2019 ). In addition, adaptive behavior has been shown to be amenable to treatment in children with developmental disabilities (Matson et al, 2012 ; Bal et al, 2015 ; Duncan et al, 2018 ), making it a particularly appealing endpoint for targeted interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In young children, adaptive behavior measures consider a wide range of developmentally relevant constructs known to affect early childhood outcomes, such as executive functioning, behavioral inhibition, social-emotional skills, and pre-academic skills (Luckasson et al, 2002 ; Sparrow et al, 2005 ; Oakland and Harrison, 2008 ). Thus, adaptive behavior may serve as a proximal indication of how an individual functions within developmentally relevant contexts and provide additional information important for conceptualizing the profile of risk of an individual child and resilience in their specific environment (Test et al, 2009 ; Bal et al, 2015 ; Dell'Armo and Tassé, 2019 ). In addition, adaptive behavior has been shown to be amenable to treatment in children with developmental disabilities (Matson et al, 2012 ; Bal et al, 2015 ; Duncan et al, 2018 ), making it a particularly appealing endpoint for targeted interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Future research should focus more directly on parent expectations for their child(ren) saving behaviors. Recent research suggests that adaptive behavior (i.e., conceptual, social, and practical skill) may be an instrumental factor in post-school success for young adults with intellectual disabilities who have poor adaptive skills, regardless of parents' expectations (Dell'Armo & Tassé, 2019). In future research, it would be helpful to include adaptive behavior assessments and more direct questions about the level of parent/guardian involvement in the finances of their youth with disabilities to better understand the causal relationship between disability type and amount saved.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that students with better social skills had improved outcomes in postsecondary education attendance and employment. In a sample of participants with intellectual disability, Dell'Armo and Tassé (2019) found that adaptive behavior variables (social skills, academic performance, and functional skills) were more predictive of postschool outcomes than parent expectations or demographic factors such as race, household income, and parent education level. In a sample with ASD, adaptive behaviorparticularly the Daily Living Skills subscale of the Vineland Adaptive Behavior Scaleswas most closely correlated with positive adult outcomes (Farley et al 2009).…”
Section: Current Knowledgementioning
confidence: 98%